Prevalence and antibiotic resistance profiles of Staphylococcus sp. isolated from food, food contact surfaces and food handlers in a Moroccan hospital kitchen. (11th February 2020) - Benjelloun Touimi, G.; Bennani, L.; Berrada, S.; Moussa, B.; Bennani, B.
Abstract: Food poisoning risk related to the consumption of contaminated food with known foodborne pathogens or antibiotic‐resistant bacteria is currently a serious threat for public health. Thus, pathogenic methicillin‐resistant Staphylococcus strains are considered as one of the major cause of foodborne diseases in hospitals. The present study aims to determine the prevalence and the antibiotic resistance patterns of Staphylococcus in various types of hospital food samples, work surfaces and its carriage by food handlers. A total of 608 collected samples including 300 food samples, 238 food contact surfaces and 70 nasal and hand samples were tested. The identified Staphylococcus and their antibiotic resistance patterns were analysed using the agar disk‐diffusion and PCR method was used for mecA resistance gene amplification. The prevalence of S. aureus and the coagulase‐negative staphylococci were 17·33 and 23·33%, respectively. The antibiotic resistance reached 100% towards oxacillin and Penicillin G for both S. aureus and CoNs. The mecA gene was detected in 5·71% (4/70) and 7·69% (4/52) of S. aureus and CoNs strains, respectively. The outcome of this study enlightens isolation of MRSA strains and resistant CoNs from food, food contact surfaces and food handlers. The presence of this resistant species in this critical setting, where products were intended to vulnerable and immunocompromised patients, represents a serious threat to this community. It can be a source of nosocomial infection and more precautions must be taken to prevent staphylococci food contamination mainly in hospitals. Significance and Impact of the Study: This is the first study describing the antibiotic resistance patterns of Staphylococcus aureus and coagulase‐negative Staphylococcus isolated from hospital food, food contact surfaces and food handlers samples in a Moroccan hospital kitchen. High levels of multi‐resistance were reported. The alarming outcome of this study emphasizes the crucial need of implementing an approach to fight multidrug‐resistant staphylococci mainly in healthcare settings, where the community have already compromised health issues. Abstract : Significance and Impact of the Study : This is the first study describing the antibiotic resistance patterns of Staphylococcus aureus and coagulase‐negative Staphylococcus isolated from hospital food, food contact surfaces and food handlers samples in a Moroccan hospital kitchen. High levels of multi‐resistance were reported. The alarming outcome of this study emphasizes the crucial need of implementing an approach to fight multidrug‐resistant staphylococci mainly in healthcare settings, where the community have already compromised health issues.